Status anaerobic energy sprinters qualified for the effects of a means of rehabilitation - Andriy Yefremenko (Kharkiv State Academy of Physical Culture, 2014)
Purpose: we determined the effect of the complex on the functional recovery of the state and dynamics of special physical qualities sprinters. Material and methods: the study involved 15 trained sprinters. Power anaerobic muscular activity was assessed using the battery of tests known. We have determined the ability of muscles, which reflects the potential for the rapid mobilization of productive resources systems sprinters. Results: dynamics of the special physical readiness test for the autumn-winter preparation period was positive and was at a high level, which was the key to improving athletic performance in a group of runners, sprinters, which was tested. Conclusions: revealed that the proposed complex of recovery has led to the growth rates of the special physical preparedness and capacity anaerobic power.